TiO2 nanoparticles immobilized on mortar spheres as a strategy for efficient photocatalyst reuse: new UV reactor design for dye removal - Cob-Cantú, J. R.; López-Velázquez, K.; Ronderos-Lara, J. G.; Hoil-Canul, E. R.; Castillo-Quevedo, C.; Maldonado-López, L. A.; Cabellos-Quiroz, J. L. (Frontiers in Chemistry, 2025)
TiO2 nanoparticles were immobilized on mortar spheres and subsequently packed into a tubular reactor equipped with a concentrical submergible UV lamp for photocatalytic decolorization of aniline blue solution. The microstructure and chemical composition of TiO2 layer on the spheres, the efficiency for aniline decolorization, and the durability of the TiO2 coating were studied. In this work, the mean thickness of the TiO2 layer was 4.01 ± 0.55 µm, while the mean mass loading on the substrate was 5.6 ± 0.61 mg/cm2. Then, the photocatalytic reactor showed excellent performance for dye removal, reaching levels between 95%–97% in 150 min under UV light. Moreover, by radical scavenging experiments, h+, O2.-, and ⋅OH were identified as the main reactive species. Even after twenty consecutive cycles, the removal efficiencies were higher than 83% and the decrease of efficiency was related to the partial detachment of the TiO2 layer (mean thickness decreased to 2.17 µm) which was verified by FESEM-EDX and metallographic microscopy. Finally, based on results, it is worth noting that the effective immobilization of TiO2 photocatalyst on the mortar spheres as substrate facilitates catalyst recovery, improves recyclability, and enables continuous water treatment. Therefore, this technology is a promising option for the removal of dyes in water, we even suggest that the proposed photocatalytic reactor could be scaled up for the treatment of effluents from textile industries, contributing to the abatement of water pollution.